2012
DOI: 10.1258/jtt.2012.120501
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the assessment and diagnosis of musculoskeletal elbow disorders using telerehabilitation

Abstract: We examined the validity and reliability of a physiotherapy examination of the elbow, using telerehabilitation. The patho-anatomical diagnoses, systems diagnosis and physical examination findings of face-to-face physiotherapy examinations were compared with telerehabilitation examinations. Ten participants attended a single session, during which they were interviewed, a face-to-face physical examination was performed and a remote physical examination was conducted, guided by an examiner at a different location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
158
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(164 citation statements)
references
References 14 publications
3
158
0
3
Order By: Relevance
“…Six of the eight studies in physiotherapy [ 41 , 43 47 ] and one in occupational therapy [ 48 ] were also from the UQ group. Similar patterns were evident to the speech pathology applications: (a) varied problems (e.g., knee, shoulder, elbow problems) across client groups (e.g., Parkinson’s Disease, Cystic Fibrosis); and (b) use of similar telerehabilitation components, again with low band-width telephone dial-up or wireless technology connecting parties within the same building.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six of the eight studies in physiotherapy [ 41 , 43 47 ] and one in occupational therapy [ 48 ] were also from the UQ group. Similar patterns were evident to the speech pathology applications: (a) varied problems (e.g., knee, shoulder, elbow problems) across client groups (e.g., Parkinson’s Disease, Cystic Fibrosis); and (b) use of similar telerehabilitation components, again with low band-width telephone dial-up or wireless technology connecting parties within the same building.…”
Section: Resultsmentioning
confidence: 99%
“…Similar patterns were evident to the speech pathology applications: (a) varied problems (e.g., knee, shoulder, elbow problems) across client groups (e.g., Parkinson’s Disease, Cystic Fibrosis); and (b) use of similar telerehabilitation components, again with low band-width telephone dial-up or wireless technology connecting parties within the same building. Most studies focused on agreement across delivery modes in terms of diagnostic assessments and intra- and inter-reliability for on-line ratings or evaluations [ 43 46 ], with another two studies in physiotherapy conducted at La Trobe University [ 49 , 50 ], one of which demonstrated a similar focus and findings [ 49 ]. Designs employed were mostly repeated measures across remote and face-to-face conditions [ 43 46 , 49 ], with descriptive outcome statistics provided in one study [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the recent advancements in ICT, pilot studies on the telerehabilitation assessment of stroke survivors have been increasing (6). The validity and the reliability of telerehabilitation assessment have mainly been reported in terms of the areas of pain, swelling, the range of motion of joints, muscle strength, balance, gait, posture, special orthopedic testing, and neurodynamic testing, mostly using video conference systems (8,(10)(11)(12)(13). The studies mentioned above have two main limitations: The first is that ROM and muscle strength show high validity, whereas posture, special orthopedic testing, and neurodynamic testing have low to moderate validity.…”
Section: Introductionmentioning
confidence: 99%
“…This is important for evaluating the effectiveness of physical therapy, deciding whether to treat spasticity with Botox injection and medication, and evaluating the effectiveness after treatment (14,15). However, few studies have evaluated spasticity in telerehabilitation assessment, and the validity of neurodynamic tests is reported to be relatively low (10,11,13,16).…”
Section: Introductionmentioning
confidence: 99%